Effect of Neonatal Nurses' Attitudes to Death on Palliative Care - Ayşe Arıcıoğlu Sülün; Emriye Hilal Yayan; Maksude Yıldırım (Galenos Yayinevi, 2021)
Introduction:Neonatal palliative care is administered with compassion to minimize the suffering of the newborn and its family. Neonatal intensive care nurses are unable to provide adequate care to the patient by developing an attitude towards death and are able to experience a sense of failure. There is insufficient knowledge and experience about neonatal nurses' responses to death and the effect of these responses on applied palliative care. Based on these data, this study was conducted to determine the status of neonatal intensive care nurses' attitudes towards death affecting their palliative care.Methods:The sample of our research consists of five provinces selected by simple random sampling method. Ninety-six neonatal nurses participated in the study. The research data were collected using the ''neonatal palliative care attitude scale (NPAS)", "death attitude scale (DAS)'' and ''introductory features form'' prepared by the researcher. In the analysis of the data, descriptive statistics, t-test, Kruskal-Wallis test were used to evaluate continuous and counting variables.Results:As a result of the correlation analysis, there was a low negative correlation between the total score of NPAS and the total score of DAS and between the sub-dimension of NPAS organization and the sub-dimension of DAS escape acceptance. There is a significant relationship between nurses' palliative care practices and their marital status, infant loss status and diversity of institutions.Conclusion:There is a low association between the sub-dimension of escape acceptance associated with death related to neonatal palliative care and the sub-dimension of organization (r=-0.225). This result can be interpreted as nurses have difficulty in giving palliative care to babies when they develop a negative attitude towards death. The remarkable aspect of this finding is that the participants in our study were nurses working in the neonatal intensive care, which is a specific unit.